Contemporary decongestant practices of Canadian otolaryngologists for endoscopic sinus surgery - Jonathan W. Reid; Brian W. Rotenberg; Leigh J Sowerby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Cocaine has traditionally been the topical decongestant most frequently used for visualization of the surgical field in Endoscopic Sinus Surgery (ESS). Alternatives include xylometazoline, oxymetazoline, and epinephrine. The understanding of the safety profile of each agent is changing, as are the practices of Otolaryngologists-Head & Neck Surgeons. The objective of this study is to determine decongestant use practices in ESS across Canada, which has not previously been studied. Methods A cross-sectional survey design using a 24-item electronic questionnaire was distributed to actively practicing members of the Canadian Society of Otolaryngology-Head and Neck Surgery via email. A French translated version of the survey was also available. Questions explored the respondents’ demographics and decongestion practices for ESS. Results Ninety-six surveys from otolaryngologists practicing in Canada were completed (19% response rate). The average time in practice was 16.5 years (range 1–50 years, SD 12.0 years). Twenty-six (27%) of respondents use some form of cocaine solution for topical decongestion in ESS. Over a total of over 1500 combined practice-years, eight respondents (8%) personally experienced an adverse event that could be attributed to cocaine, including two mortalities. One cardiac even was directly attributable to the patients’ use of recreational cocaine in the immediate pre-operative period. Conclusion The popularity of cocaine for topical decongestion in ESS in present-day Canada is less than in surveys from other countries. However, there are few reported adverse events with long-term consequences that are attributable to intraoperative cocaine. Considering the beneficial effects of cocaine for visualization and pain control, this change in practice warrants further investigation.